2021
DOI: 10.1101/2021.02.24.432792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In situ single-cell activities of microbial populations revealed by spatial transcriptomics

Abstract: Microbial populations and communities are heterogeneous, yet capturing their diverse activities has proven challenging at the relevant spatiotemporal scales. Here we present par-seqFISH, a targeted transcriptome-imaging approach that records both gene-expression and spatial context within microscale assemblies at a single-cell and molecule resolution. We apply this approach to the opportunistic bacterial pathogen, Pseudomonas aeruginosa, analyzing ~600,000 individuals across dozens of physiological conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…strains ( Table 1 ), which corroborates the performance of this probe, providing a suitable alternative for studies in pure cultures but also in biofilms. The main advantage of using PNA rRNA probes is related with the visualization of the whole cells and spatial distribution and metabolic activity of the cells [ 45 ], allowing a better knowledge of the organization and functional development of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…strains ( Table 1 ), which corroborates the performance of this probe, providing a suitable alternative for studies in pure cultures but also in biofilms. The main advantage of using PNA rRNA probes is related with the visualization of the whole cells and spatial distribution and metabolic activity of the cells [ 45 ], allowing a better knowledge of the organization and functional development of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent developments combining barcoding with fluorescence in situ hybridization have increased the spatial resolution at which cell lineage can be traced [ 135 ] and dual-view light sheet microscopy has made it possible to track entire cell populations in real time without interruption [ 127 , 136 ]. Finally, advances in spatial transcriptomics make it possible to simultaneously examine the expression of hundreds of genes in space, which, for instance, revealed that bacteria cells can express vastly distinct expression profiles within the same colony [ 137 ]. Currently, most of the above technologies are applied to study a few genetically tractable model organisms, but they hold the promise of uncovering many still hidden forms of multicellular organization in nonmodel organisms as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these single-cell technologies, earlier this year the Newman and Cai laboratories at Caltech successfully generated spatial single-cell bacterial transcriptomics in Pseudomonas aeruginosa using a microscopical approach. This dataset probed a large number of cells (∼600,000) but limited the transcript coverage to 105 genes ( Dar et al, 2021 ) as opposed to studies done at the full transcriptome scale. In order to identify distinct cellular states in bacteria with inherently low abundance of transcripts, capturing the highest number of transcripts and number of cells are the two most critical parameters.…”
Section: Discussionmentioning
confidence: 99%